Wewenang Majelis Pengawas Daerah (MPD) Pasca Putusan Mahkamah Konstitusi Nomor 49/PUU-X/2013 Dalam Rangka Meningkatkan Kualitas Notaris - Aryani Witasari (Jurnal Hukum, 2015)
Abstract               Notary is a state official who works in the lift by the Ministry of Justice and Human Rights, she serves people who need assistance services in terms of making a deed. Deed that has been made by a Notary under the legislation referred to an authentic deed, have the force of law and can be used as evidence when required. In order to conduct guidance and supervision of the performance of the Notary, required an institution assigned by law (UU No. 2 / 2014 on amendments to UU No. 30/ 2004 concerning Notary) , the agency called the Council of Trustees of Regions (MPD). Pursuant to Article 66 of Law No. 30 of 2004 Regional Supervisory Council is authorized to carry out the task of supervision on the performance of the Notary , to the benefit of the judicial process ,investigator , prosecutor or judge must be approved by the MPD and will take a copy of the minutes and certificates or letters attached to the minutes of a notary deed or protocol of storage , as well as when to call the notary to attend the hearings related to the deed prepared or protocols that are in storage Notary Public Notary . Based on the decision of the Constitutional Court Number 49 / PUU - X / 2013 ), the MPD no longer has the authority to give consent to the law enforcement if it will call the Notary related to their work , but by the Law on the switch to the Court of Honor , which until today Court of Honor was not yet in shape. Keywords : Notary, The Council of Trustees of Regions (MPD), Decision of The Constitutional Court Abstrak Notaris merupakan pejabat negara yang bekerja diangkat oleh Kementrian Hukum dan Hak Azasi Manusia, dia melayani masyarakat yang memerlukan bantuan jasanya dalam hal pembuatan suatu akta. Akta yang telah dibuat oleh seorang Notaris berdasarkan undang-undang disebut dengan akta otentik, mempunyai kekuatan hukum dan dapat dijadikan sebagai alat bukti manakala diperlukan. Dalam rangka untuk mengadakan pembinaan dan pengawasan terhadap kinerja Notaris, diperlukan suatu lembaga yang ditugasi oleh undang-undang(Undang-undang no 2 tahun 2014 tentang perubahan atas Undang-undang no 30 tahun 2004 tentang Jabatan Notaris), lembaga tersebut bernama Majelis Pengawas Daerah (MPD). Berdasarkan Pasal 66 UU Nomor 30 tahun 2004 Majelis Pengawas Daerah (MPD) diberi kewenangan untuk menjalankan tugas pembinaan dan pengawasan terhadap kinerja Notaris, untuk kepentingan proses peradilan, penyidik, penuntut umum atau hakim harus mendapat persetujuan dari MPD manakala akan mengambil fotocopi minuta akta dan atau surat-surat yang dilekatkan pada minuta akta atau protokol Notaris dalam penyimpanan Notaris, begitu pula jika akan memanggil Notaris untuk hadir dalam pemeriksaan yang berkaitan dengan akta yang dibuatnya atau protokol Notaris yang berada dalam penyimpanan Notaris. Berdasarkan putusan Mahkamah Konstitusi Nomor 49/PUU-X/2013), maka MPD tidak lagi memiliki kewenangan untuk memberi persetujuan kepada para penegak hukum jika akan memanggil Notaris berkaitan dengan pekerjaannnya, tetapi oleh Undang-undang di alihkan kepada Mahkamah Kehormatan, yang sampai saat ini Mahkamah Kehormatan itu belum juga di bentuk. Kata kunci: Notaris, Majelis Pengawas Daerah (MPD), Putusan Mahkamah Konstitusi